2010
DOI: 10.1002/cbf.1682
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of fluoxetine: Studies in mice melanoma model

Abstract: In vivo effects of the antidepressant fluoxetine on spleen antioxidant status of C57BL/6 mice were studied using a melanoma experimental model. After a 14-day treatment with fluoxetine (10 mg kg À1 day À1 , i.p.), the endogenous antioxidant non-enzyme (glutathione) and enzyme (superoxide dismutase (SOD) and glutathione peroxidase (GPx)) defense systems in spleen of healthy animals were not changed; the lipid peroxidation (LP) was also unchanged. When B16F10 melanoma cells were introduced in C57BL/6 mice 2 h be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Fluoxetine also significantly inhibited INDO-and ethanol-induced increases in MPO levels here; this outcome was in agreement with a previous study that demonstrated an inhibitory effect of fluoxetine on MPO levels in irritable bowel syndrome (Kato et al 1998). Fluoxetine also is known to inhibit the depletion in GSH to counter oxidative stresses produced during ulcer formation (Kirkova et al 2010). This antioxidant effect of fluoxetine might be related to the fact the drug causes increases in levels of serotonin (which itself imparts an anti-oxidant effect; Ham et al 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Fluoxetine also significantly inhibited INDO-and ethanol-induced increases in MPO levels here; this outcome was in agreement with a previous study that demonstrated an inhibitory effect of fluoxetine on MPO levels in irritable bowel syndrome (Kato et al 1998). Fluoxetine also is known to inhibit the depletion in GSH to counter oxidative stresses produced during ulcer formation (Kirkova et al 2010). This antioxidant effect of fluoxetine might be related to the fact the drug causes increases in levels of serotonin (which itself imparts an anti-oxidant effect; Ham et al 1999).…”
Section: Discussionsupporting
confidence: 93%
“…In these epithelial cells, it induces an increase in serotonin (5-HT) levels by blocking L-monoamine oxidase and serotonin reuptake transporters [41][42][43] . On the other hand, FLX has been shown to interfere with the OS machinery in experimental models and humans [44][45][46][47][48][49][50][51][52][53][54][55] . Treatment with FLX was found to reduce malondialdehyde (MDA) and carbonyl levels in stressed rats, whilst it enhanced superoxide dismutase (SOD), catalase, glutathione S-transferase, glutathione reductase and glutathione contents [45,46] .…”
Section: Antidepressant Flx Modulates Oxidative Stressmentioning
confidence: 99%
“…We have already demonstrated that FLX treatment arrested colon tumor cells within the G0/G1 cell-cycle phase without inducing DNA damage [64] . Then, FLX was shown to reduce ROS generation, reversing the melanoma-induced tissue oxidation in mice [50] . In brain tissue of tumor-bearing mice, FLX treatment further reduced OS, enhancing the SOD activity [49] .…”
Section: Flx Takes Energy Generation Un-der Control To Reduce Malignamentioning
confidence: 99%
See 2 more Smart Citations